Peran Guru dalam Menerapkan Nilai Karakter Kedisiplinan dalam Meningkatkan Kegiatan Belajar Siswa di SD Al-Ma’soem - Hanik, Elya Umi; Yunita, Vera Dina; Putri, Hapsari Cahyaning; Sirriyah, Mia Mukhlisiyyatus; Machaasinaty, Tsamara; Khasanah, Fitri Noor (MASALIQ, 2022)
This study aims to analyze the teacher's role in applying the value of disciplinary character in improving student learning activities at Al-Ma'soem Elementary School by combining the national curriculum and field of study (diniyyah) and developed through the principles of discipline and religion. Learning is not always interpreted as something but a flexible concept that develops and follows the demands of education as well as the needs of science and technology inherent in the form of human resource development. By looking at the way of learning at SD al-Ma'soem which cannot be separated from implementing discipline that can affect the intensity of student learning. The reward and punishment method is something that most people or institutions require in education, one of which is at Al-ma'soem Elementary School. This is considered as one of the solutions to overcome disciplinary problems and improve student achievement. The teacher to carry out the improvement of the teaching and learning process by applying the value of the character of discipline is very important and becomes a top priority. This is done so that students return to their enthusiasm for learning. This study aims to analyze the teacher's role in applying the value of the character of discipline in improving student learning activities at Al-Ma'soem Elementary School.